2014
DOI: 10.1179/1743285514y.0000000077
|View full text |Cite
|
Sign up to set email alerts
|

Froth stability of coal flotation in saline water

Abstract: The objective of this study was to identify a practical solution to mitigating over-stable froth problems in fine coal flotation in saline water. The effect of coal particle size, water quality and chemical reagents which can be manipulated in flotation plants, on the froth stability and coal flotation performance was investigated. It was found that froth stability was dependent on the coal particle size, the proportion of process water mixed with de-ionised water and the dosage of the collector or frother. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…However, the concentrate yield was the lowest for the <74 lm size fraction. The flotation speed of the 125-74 lm size fraction was the fastest which was in line with other literature (Aktas et al, 2008;Tao et al, 2009;Xie et al, 2009;Zhang et al, 2013;Wei et al, 2014). It indicates that particles of small size are more helpful to increase the froth stability.…”
Section: Resultssupporting
confidence: 91%
“…However, the concentrate yield was the lowest for the <74 lm size fraction. The flotation speed of the 125-74 lm size fraction was the fastest which was in line with other literature (Aktas et al, 2008;Tao et al, 2009;Xie et al, 2009;Zhang et al, 2013;Wei et al, 2014). It indicates that particles of small size are more helpful to increase the froth stability.…”
Section: Resultssupporting
confidence: 91%
“…In the previous study, overly stable froth was obtained with 50% air recovery when saline water with a medium conductivity was tested in line with the observation in the plant (Wei et al, 2014). The normal air recovery at which froth is not overly stable is below 35%.…”
Section: Combustible Matter Recoverysupporting
confidence: 67%
“…These works highlight the relative effect of the addition of salt, which can be either detrimental or beneficial to foam stability. However, in the flotation of coal, solutions of higher ionic strength showed improved froth stability (Kurniawan et al, 2011;Farrokhpay and Zanin, 2012;Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…flotation recovery and yield) there is also an operational incentive for the study of the impact of salts on bubble stability. For instance, it is reported that overly-stable froths cause frothing in pump boxes, tanks, and thickeners, which commonly disrupt plan operation in Australian CHPPs (Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%